Coarse bauxite residue for roadway construction materials - Jitsangiam, Peerapong; Nikraz, Hamid (Taylor & Francis, 2012)
About 25 million tonnes of bauxite residue (BR) from alumina refining are generated in Australia each year. Managing this residue is costly, and the reuse of coarse BRs is becoming an increasingly attractive and sustainable solution to the problem. Using coarse BR in road construction has the potential for large volume reuse. This study investigated whether coarse BR is a viable road base material in Western Australia. A pozzolanic-stabilised mixture was created to improve the properties ofthe residue to satisfy the minimum requirements for road base. Laboratory tests for resilient modulus and permanent deformation were then carried out. Comparisons were made between the stabilised residue and conventional road base material used in Western Australia. The performance of the stabilised residue was superior to that of the conventional material, which can provide improved performance when used as road base material in Western Australia.